Narrating future economies in Saudi Arabia: A discourse-historical analysis of identity, modernity, and risk - Sa’di, Rami A; Khasawneh, Asma Jadallah; Ismail, Sayed M; Koka, Nisar Ahmad (Research Journal in Advanced Humanities, 2026)
This article develops a discourse-historical account of how Saudi Arabia's transition from an oil-centered economy to a set of future-oriented economic imaginaries that can be studied as institutional discourse. Rather than treating future economies as self-evident policy objects, the article argues that they are narrated through historically situated claims about national identity, modernity, and risk. Drawing on the Discourse-Historical Approach, critical policy discourse studies, sociotechnical imaginaries, and cultural political economy, the article proposes an Identity-Modernity-Risk Narrative Model for analyzing official Saudi institutional texts related to Vision 2030 and associated transformation programs. The article is conceptual and methodological: it does not claim to report the results of a finalized corpus analysis, but it provides a rigorous framework for future empirical work using a curated corpus of Vision 2030 documents, national transformation materials, sovereign investment communication, and future-economy project texts. The central argument is that future-economy discourse makes transformation intelligible by anchoring it in national continuity, desirable by framing it as innovation and global competitiveness, and urgent by representing oil dependency, inaction, and global technological competition as manageable risks. The article contributes to discourse studies by linking DHA strategies, argumentative topoi, and future-oriented policy narratives in one model. It also contributes to Saudi Vision 2030 research by showing that economic transformation is not only institutional and material, but also narrative, linguistic, and historically legitimized.